SECONDARY SCHOOL TEACHERS’ TRAIT EMOTIONAL INTELLIGENCE, JOB SATISFACTION, AND SELFEFFICACY - Tabigat, Akhyerkye (Nazarbayev University Graduate School of Education, 2022)
Research concerned with the relationship between trait emotional intelligence (EI) and academic success of both students and teachers has been an emerging topic in educational settings in the last decade. Although a vast body of studies promotes trait emotional intelligence as a reasonable factor contributing to students’ success, little is known about teachers’ associated success, particularly in Central Asian countries. This research study aims to identify the relationship between the trait emotional intelligence, job satisfaction, and self-efficacy of secondary school teachers in the context Nur-Sultan city, Kazakhstan. The study adopts a cross-sectional research design and makes use of descriptive statistics, confirmatory factor analysis (CFA), and structural equation modelling (SEM). The Trait Emotional Intelligence Questionnaire Short Form (TEIQue-SF) and the OECD questionnaires were administered to a sample of 107 secondary school teachers from a total of 11 separate public schools (n = 97) and three separate private schools (n = 10). The findings of this study demonstrate that Well-being, Self-control, Self-efficacy (Instructional Strategies), Self-efficacy (Classroom Management), and Job satisfaction factors are reflective of the cultural context and capture the experiences of teachers in the Kazakhstani context. Though the findings are not conclusive, a better understanding and exploration of the concepts may be carried out with a larger sample of teachers from multiple regions inside Kazakhstan and in other post-Soviet jurisdictions. The results also indicate a strong correlation between Self-efficacy for classroom management and instructional strategies. Considering the strong correlation between trait emotional intelligence factors, Well-being and Self-Control and Job satisfaction, it is proposed that a key policy priority should therefore be to plan for the long-term support for the well-being and self-control of teachers in Kazakhstani society in order to increase their job satisfaction level of retention. Keywords: trait emotional intelligence (EI), teacher self-efficacy, job satisfaction
Keywords: trait emotional intelligence; EI; teacher self-efficacy; job satisfaction; Type of access: Open Access